Short Interfering RNA Inhibits Rift Valley Fever Virus Replication and Degradation of Protein Kinase R in Human Cells - Faburay, Bonto; Richt, Juergen A. (Frontiers in Microbiology, 2016)
Rift Valley fever virus (RVFV) is a mosquito-borne zoonotic pathogen causing severe outbreaks in humans and livestock in sub-Saharan Africa and the Arabian Peninsula. Human infections are characterized by fever, sometimes leading to encephalitis, retinitis, hemorrhagic fever and occasionally death. There are currently no fully licensed vaccines or effective therapies for human use. Gene silencing mediated by double-stranded short interfering RNA (siRNA) is a sequence-specific, highly conserved mechanism in eukaryotes, which serves as an antiviral defence mechanism. Here, we demonstrate that siRNA duplexes directed against the RVFV nucleoprotein can effectively inhibit RVFV replication in human (MRC5 cells) and African green monkey cells (Vero E6 cells). Using these cells, we demonstrate that individual or complex siRNAs, targeting the RVFV nucleoprotein gene completely abrogate viral protein expression and prevent degradation of the host innate antiviral factor, protein kinase R (PKR). Importantly, pre-treatment of cells with the nucleoprotein-specific siRNAs markedly reduces the virus titer. The antiviral effect of the siRNAs was not attributable to interferon or the interferon response effector molecule, protein kinase R. Thus, the antiviral activity of RVFV nucleoprotein-specific siRNAs may provide novel therapeutic strategy against RVFV infections in animals and humans.